Vonós hangszerek Afrikában - Brauer-Benke, József (Afrika Tanulmányok / Hungarian Journal of African Studies, 2022)
A survey of the available historical data allows one to show that the appearance and adoption of bowed string instruments in the different cultural regions of Africa took place in different periods and owing to different influences. After this instrument category had appeared in Central Asia in the 9th century, it spread to the eastern lands of the Arab world (Mashriq) in the 10th century, and thence to the western lands of the Arab world (Maghrib) in the course of the 12th to 13th centuries. The so-called rebab fiddle type (carved of a single piece of wood and provided with a body made of a coconut shell) was modified by the peoples of West Africa so that it had a body made of the locally abundant large calabash, while the peoples of northeastern Africa adopted various relatives of the kamanja fiddle type (having a box-like body), such as the Ethiopian masenko and the Eritrean wat’a. Contrastingly, the Swahili cultural region adopted the fiddle type having a pipe-shaped body, characteristic of the Far East and Southeast Asia, from the Chinese merchants and explorers of the early 15th century, an instrument type later carried by Swahili trading caravans into Central Africa and the southern parts of East Africa. Although the southernmost portion of South Africa is home to seemingly very archaic bowed string instruments, European cultural influences have been a definite factor in this region since the mid-17th century. It is unsurprising, then, that an etymological analysis of ostensibly archaic string instruments reveals the impact of European bowed instruments through stimulus diffusion, i.e. the local adoption of the idea of a bow and its adaptation to indigenous instruments previously played with hitting the strings or rubbing them with sticks. In comparison to other instruments of West Africa, bowed instruments have barely survived modernization and, obsolete as they now are, play little role on the stages of world music. This process was exacerbated by the influence of the Islamic reform movements of the 19th century that deemed them barely tolerated or even prohibited instruments because of their associations with the pre-Islamic era; this had already gradually reduced their use in the two centuries preceding the modernization of the 20th century. The use of bowed string instruments has also declined significantly in eastern ands Africa. It is only in the North African region that bowed string instruments enjoy continuing popularity. For example, they are still used widely by the rural folk orchestras of Egypt, while in Morocco the rebab has been modernized for classical Arabic music by adopting certain parts of the European fiddle (e.g. tailpiece, bridge, fingerboard). The European fiddle was also adopted wholesale in North Africa; so that European and traditional instruments are now employed simultaneously by many Algerian orchestras. (image 22) It is remarkable that European fiddles are played in a vertical position in this context, a playing technique usual for folk fiddles; the potential playing techniques inherent in the shape of the European fiddle are thus not utilised at all.